Activation of Hedgehog signaling by the oncogenic RELA fusion reveals a primary cilia-dependent vulnerability in supratentorial ependymoma. Issue 1 (31st May 2022) - de Almeida Magalhães, Taciani; Alencastro Veiga Cruzeiro, Gustavo; Ribeiro de Sousa, Graziella; Englinger, Bernhard; Fernando Peinado Nagano, Luis; Ancliffe, Mathew; Rodrigues da Silva, Keteryne; Jiang, Li; Gojo, Johannes; Cherry Liu, Yulu; Carline, Brooke; Kuchibhotla, Mani; et al.
Abstract: Background: Supratentorial RELA fusion (ST-RELA) ependymomas (EPNs) are resistant tumors without an approved chemotherapeutic treatment. Unfortunately, the molecular mechanisms that lead to chemoresistance traits of ST-RELA remain elusive. The aim of this study was to assess RELA fusion-dependent signaling modules, specifically the role of the Hedgehog (Hh) pathway as a novel targetable vulnerability in ST-RELA. Methods: Gene expression was analyzed in EPN from patient cohorts, by microarray, RNA-seq, qRT-PCR, and scRNA-seq. Inhibitors against Smoothened (SMO) (Sonidegib) and Aurora kinase A (AURKA) (Alisertib) were evaluated. Protein expression, primary cilia formation, and drug effects were assessed by immunoblot, immunofluorescence, and immunohistochemistry. Results: Hh components were selectively overexpressed in EPNs induced by the RELA fusion. Single-cell analysis showed that the Hh signature was primarily confined to undifferentiated, stem-like cell subpopulations. Sonidegib exhibited potent growth-inhibitory effects on ST-RELA cells, suggesting a key role in active Hh signaling; importantly, the effect of Sonidegib was reversed by primary cilia loss. We, thus, tested the effect of AURKA inhibition by Alisertib, to induce cilia stabilization/reassembly. Strikingly, Alisertib rescued ciliogenesis and synergized with Sonidegib in killing ST-RELA cells. Using a xenograft model, we show that cilia loss is a mechanism for acquiring resistance to the inhibitory effect of Sonidegib. However, Alisertib fails to rescue cilia and highlights the need for other strategies to promote cilia reassembly, for treating ST-RELA tumors. Conclusion: Our study reveals a crucial role for the Hh pathway in ST-RELA tumor growth, and suggests that rescue of primary cilia represents a vulnerability of the ST-RELA EPNs.